KEPEMIMPINAN DI LEMBAGA PENDIDIKAN AL-QUR’AN: EKSPLORASI MODEL DAN GAYA KEPEMIMPINAN - Subhan, Ah. (STAI AL FALAH Banjarbaru, 2024)
AbstractThis research aimed to explore effective leadership models and styles at the al-Qur'an Al-Hidayah Kuala Kapuas Institution, which has programs including Taman Pendidikan al-Qur’an, Tahfiz al-Qur'an, and Formal Education Early age. It was founded in 2003, the institution had succeeded in producing Qur'anist generations who were fluent in reading the Qur'an at an early age and had achieved achievements in the Kapuas Regency. It used a qualitative field research approach. Then, data collection techniques were carried out using non-participant observation, interviews, and documentation. The data were analyzed through several stages, namely; display data, reduction, and concluding. The main research findings regarding leadership models and styles at the Al-Hidayah Kuala Kapuas Al-Qur'an Education Institute had three elements of leadership model, namely, leader-member relations, and teachers following the directions given by the leader. Task structure, providing procedural solutions to obstacles. Position power, providing regular forums, evaluating and supporting recommendations from teachers. Meanwhile, the leadership style contained four dimensions, namely, Idealized influence, equal treatment for all teachers, Inspirational motivation, holding competitions between teachers and students as well as familiarizing teachers giving prizes to students, Simultaneous intellectual, holding weekly meetings to prepare for teaching and learning and making learning props together, Individualized consideration, inviting all teachers to exchange opinions about learning problems. Keywords: Al-Qur'an Educational Institution, Leadership Model, Leadership Style. AbstrakPenelitian ini bertujuan, menggali model dan gaya kepemimpinan yang efektif di Lembaga al-Qur’an al-Hidayah Kuala Kapuas. Mempunyai program pendidikan antara lain Taman Pendidikan Al-Qur’an, Tahfiz al-Qur’an dan pendidikan anak usia dini pada jalur Formal. Lembaga yang berdiri sejak tahun 2003 ini, telah berhasil mencetak generasi qur’ani yang fasih membaca al-Qur’an untuk usia dini dan meraih prestasi di Kabupaten Kapuas. Penelitian ini menggunakan pendekatan Kualitatif jenis penelitian lapangan (field research). Teknik pengumpulan data dilakukan dengan observasi non-partisipan, wawancara dan dokumentasi. Analisis data dilakukan dengan tahap penyajian data, reduksi dan penarikan kesimpulan. Temuan utama penelitian tentang model dan gaya kepemimpinan di Lembaga Pendidikan Al-Qur’an Al-Hidayah Kuala Kapuas, memiliki tiga unsur model kepemimpinan yaitu, leader-member relations, para guru mengikuti arahan yang diberikan oleh pemimpin. Task structure, memberikan solusi prosedural terhadap kendala. Position power yaitu, menyediakan forum rutinan, mengevaluasi dan mendukung rekomendasi dari guru. Adapun gaya kepemimpinan, memuat empat dimensi yaitu, Idealized influence, perlakuan sama untuk semua guru. Inspirastion motivation, mengadakan Lomba antar guru dan murid juga membiasakan guru memberikan hadiah bagi siswa, Intelectual simultan, Melaksanakan rapat mingguan untuk persiapan belajar-mengajar dan membuat alat peraga pembelajaran bersama, Individualized consideration, Mengajak semua guru bertukar pendapat tentang masalah pembelajaran. Kata Kunci: Gaya Kepemimpinan, Lembaga Pendidikan al-Qur’an, Model Kepemimpinan.